Structure Optimization of Cylindrical Roller Bearing based on Orthogonal Test - Jiaming Zhang; Ming Qiu; Xiaoxu Pang; Jun Ye (Jixie chuandong)
In view of the skidding of aero-engine spindle bearings under high speed and light load and based on the construction of a simulation model of an aero-engine cylindrical roller bearing，the effects of structural parameters such as roller number，roller length，initial radial clearance and cage guide clearance on bearing skidding and fatigue life are studied . The results show that the rate of bearing skidding can be effectively reduced by increasing the number of rollers，cage guide clearance，and reducing roller length and initial radial clearance. By using the orthogonal design method，the influence weights of roller number，roller length，initial radial clearance and cage guide clearance on bearing skidding，bearing fatigue life and inner raceway wear rate are obtained. Through comprehensive balance and optimization，it is obtained that when the number of rollers，roller length，initial radial clearance and cage guide clearance are 13，6 mm，-2 μm and 1 mm respectively，the cage skidding rate is 0.29%，and the inner raceway wear rate is 5.9×10-13 m3/s，which reduce the probability of skidding and abrasion failure of the bearings while ensuring the bearing life.